2018
DOI: 10.1080/15287394.2018.1485124
|View full text |Cite
|
Sign up to set email alerts
|

Case series: rheumatological manifestations attributed to exposure to Libby Asbestiform Amphiboles

Abstract: An increased risk for Systemic Autoimmune Diseases (SAID) has been reported in Libby, Montana, where extensive exposures to fibrous amphiboles occurred due to mining and use of asbestos-laden vermiculite. In addition, positive antinuclear autoantibody tests are associated with exposure to Libby Asbestiform Amphiboles (LAA) in both humans and mice. Among 6603 subjects who underwent health screening at the Center for Asbestos Related Diseases (CARD, Libby MT), 13.8% were diagnosed with an autoimmune disease, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 52 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…The results support and extend our previous studies, which reported elevated frequencies and titers of ANA in the Libby population, as well as an increased risk for SLE, SSc, RA, and sarcoidosis (Noonan, et al 2006, Pfau, et al 2005, Diegel, et al 2018). Exposure to LAA was demonstrated to be associated with an elevated frequency of positive ANA tests in non-autoimmune prone mice and rats as well (Ferro, et al 2013, Pfau, et al 2008, Salazar, et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results support and extend our previous studies, which reported elevated frequencies and titers of ANA in the Libby population, as well as an increased risk for SLE, SSc, RA, and sarcoidosis (Noonan, et al 2006, Pfau, et al 2005, Diegel, et al 2018). Exposure to LAA was demonstrated to be associated with an elevated frequency of positive ANA tests in non-autoimmune prone mice and rats as well (Ferro, et al 2013, Pfau, et al 2008, Salazar, et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In 2006, a case-control study of self-reported SLE patients, nested within a medically screened general population cohort in Libby, MT, showed a more than 4-fold elevated risk for SLE associated with a history of greater LAA exposure via multiple environmental pathways (Noonan, et al 2006). Among the 6603 individuals who have undergone health screening at the Center for Asbestos Related Diseases (CARD, Libby MT), the frequencies of RA, SLE, sarcoidosis, and SSc are significantly higher than the published expected prevalence for these diseases in the United States (Diegel, et al 2018). However, unlike investigations of crystalline silica (Cooper, et al 2010, Pollard 2016), there are no apparent large cohort analyses of risk for SAID that establish asbestos or asbestiform structures as a trigger for autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, some groups are conducting research using asbestos-exposed individuals or animal models of autoimmune diseases, and it is expected that the results will be forthcoming. Th17 cells seem to be more strongly involved in the breakdown of self-tolerance rather than anti-tumor immunity [ 56 , 57 , 58 ]. This area requires extensive further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several different cohorts including Libby, Montana (73), Wittenoom, Western Australia (74), and Biancavilla, Sicily (75), have linked autoantibodies, including ANA, to asbestos exposure. Studies of the communities of Libby and Troy in Montana have found that almost 14% have been diagnosed with an autoimmune disease other than diabetes (76,77) and mortality to autoimmune diseases is higher than expected (78). However, a causal role for asbestos exposure in autoimmune disease has not been established due to study limitations (4), and other confounders, including the possibility of concurrent silica and asbestos exposures (2), and smoking history (79).…”
Section: Fibrous Materials Asbestosmentioning
confidence: 99%
“…Autoimmune diseases associated with Libby Asbestiform Amphibole (LAA) exposure include SLE, SSc, and RA (76,78). ANA are common and include autoantibodies against dsDNA, SS-A/Ro52, Scl70, Sm, and RNP (76). Anti-mesothelial cell antibodies, and ANA, have been linked to pleural abnormalities (85).…”
Section: Fibrous Materials Asbestosmentioning
confidence: 99%